2005
DOI: 10.1590/s1516-14392005000300023
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of fiber reinforced Polymer Concrete

Abstract: A comparative study between epoxy Polymer Concrete plain, reinforced with carbon and glass fibers and commercial concrete mixes was made. The fibers are 6 mm long and the fiber content was 2% and 1%, respectively, in mass. Compressive tests were performed at room temperature and load vs. displacement curves were plotted up to failure. The carbon and glass fibers reinforcement were randomly dispersed into the matrix of polymer concrete. An increase in compressive properties was observed as function of reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 7 publications
2
13
2
2
Order By: Relevance
“…It can be seen from these table and figure that the flexural strength increases with increasing of polystyrene. Similar behavior was found by Reis (2006).…”
Section: Ultrasonic Pulse Velocity Results (Upv)supporting
confidence: 87%
“…It can be seen from these table and figure that the flexural strength increases with increasing of polystyrene. Similar behavior was found by Reis (2006).…”
Section: Ultrasonic Pulse Velocity Results (Upv)supporting
confidence: 87%
“…Addition of glass fibres in PCC is reported to enhance the flexural strength, compressive strength, and so forth of the resulting material [18,25]. Alkali resistant macro glass fibres (Anti Crak-HP) supplied by Owens Corning India were added in PCC.…”
Section: Materials Usedmentioning
confidence: 99%
“…A number of studies on fibre reinforced polymer concrete composites (FRPCC) cite improvement in mechanical properties due to addition of fibres [15][16][17][18][19]. All of these studies have reported only the behaviour of PCC and FRPCC under statically applied loads.…”
Section: Introductionmentioning
confidence: 99%
“…In advanced industrialized countries, the utilization of fibers in concrete began in the early 1960s [1]. The type and form of fibers and also the construction of fiber-reinforced concrete (FRC) have improved significantly during the past five decades, and their employment have been on the rise [2,3]. Improving the mechanical properties of concrete using the random distribution of fibers in it has been the topic of interest of numerous research studies [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%